Why Is There Mandatory Retirement? - Lazear, Edward P. (Journal of Political Economy, 1979)
This paper offers an explanation of the use of mandatory-retirement clauses in labor contracts. It argues that the date of mandatory retirement is chosen to correspond to the date of voluntary retirement, but the nature of the optimal wage profile results in a discrepancy between spot wage and spot VMP (value of the worker's marginal product). This is because it is preferable to pay workers less than VMP when young and more than VMP when old. By doing so, the problem is solved, so the contract with mandatory retirement is Pareto efficient. A theory of agency is presented and empirical evidence which supports the hypothesis is provided.